Leflunomide Induces Dose-Dependent Lung Injury in Mice via Stimulating Vimentin and NLRP3 Inflammasome Production - El-Sherbiny, Mohamed; Atef, Hoda; Eladl, Mohamed Ahmed; Mohamed, Abdelaty Shawky; El-Shafey, Mohamed; Ali, Howaida S.; Zaitone, Sawsan A.; Alomar, Suliman Y.; Alqahtani, Saeed Awad M.; Aloyouni, Sheka Yagub; Attia, Mohammed A. (Frontiers in Pharmacology, 2021)
Recently, the therapeutic importance of the anti-rheumatic drug, leflunomide, has been increased after the involvement of leflunomide in treating other autoimmune diseases and its promising role in retarding human malignancies. Few studies have focused on the safety in human or animals without clear outlining of the pathologic features on target organs. One clinical study related leflunomide with significant pulmonary complications in predisposed individuals. The current study examined the dose-dependent lung injury produced by leflunomide in healthy mice. Albino mice were allocated into four different groups. Group (1): Vehicle control group, Group (2-4): mice received leflunomide (2.5, 5 or 10 mg/kg), respectively, for 8 weeks and then lungs were dissected from the mice for histopathological examination and fibrosis evaluation (Masson’s trichrome staining and α-smooth muscle actin immunohistochemistry). Enzyme linked immunosorbent assay was used to assess the vimentin and other inflammatory factors in the lung homogenate whereas Western blot analysis was employed to assess α-smooth muscle actin, vimentin and collagen 1. Results indicated that leflunomide induced dose-dependent pulmonary injury and the high dose and increased the vimentin, inflammatory markers (NLRP3 and interlukin-1β). Histologic examination showed distorted architecture, marked inflammatory cells infiltrate and increase collagen content. The findings were supported by Western blotting and the immunohistochemical study which showed greater pulmonary α-smooth muscle actin and vimentin content. In conclusion, the current results highlighted that leflunomide produced dose-dependent pulmonary toxicities that requires further investigation of the nature of injury.